2018
DOI: 10.1080/01443615.2018.1450368
|View full text |Cite
|
Sign up to set email alerts
|

Increased serum iron levels in pregnant women with preeclampsia: a meta-analysis of observational studies

Abstract: Our study aimed to investigate whether the serum iron levels in patients with preeclampsia were higher than in healthy pregnant women and to evaluate potential heterogeneities. We searched Pubmed, Embase, Web of Science and Medline databases for studies before September 2016. The standardised mean difference (SMD) and 95% confidence interval (CI) were used to combine results across the studies, in addition to the random-effect model. A total of 10 studies involving 363 patients with preeclampsia and 370 health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 26 publications
0
18
0
Order By: Relevance
“…Liable Fe(II) is vital for ferroptosis, as it contributes greatly to the generation of lipid peroxides. Numerous studies has confirmed that the total serum iron content is higher in patients with PE than in healthy pregnancy, with Orlov et al even reporting that the serum iron level has a direct correlation with the blood pressure level [[16], [17], [18]]. However, no study had investigated the level of Fe(II) in placental tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Liable Fe(II) is vital for ferroptosis, as it contributes greatly to the generation of lipid peroxides. Numerous studies has confirmed that the total serum iron content is higher in patients with PE than in healthy pregnancy, with Orlov et al even reporting that the serum iron level has a direct correlation with the blood pressure level [[16], [17], [18]]. However, no study had investigated the level of Fe(II) in placental tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Retrospective studies are more numerous [16,17,23,24,25,26]. Fenzl et al [25] showed significantly higher serum iron concentrations in 30 women with preeclampsia, compared to 37 healthy pregnant women.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Sarwar et al [17] found significantly lower serum iron concentrations in 50 women with preeclampsia, compared to 58 women of the control group. The meta-analysis of 10 studies conducted by Liu et al [16] provided significant evidence for higher serum/plasma iron concentrations in women with preeclampsia compared to healthy women in both the Asian and European population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Transferrin saturation also exceeded 20−50%, the limit commonly used to diagnose iron overload (Elsayed et al, 2016;Sebastiani et al, 2012). In addition to being a consequence of disorders related to iron metabolism or recurrent blood transfusions, an elevated serum iron level is also considered a risk factor for increased mortality in patients with sepsis (Lan et al, 2018), pre-eclampsia in pregnant women (Liu et al, 2019) and several types of cancers, such as liver, lung and breast (Chen et al, 2018;Wen et al, 2014). In this regard, the present experimental animal model of parenteral administration is commonly used to simulate a chronic state of iron overload in humans, regardless of the aetiology.…”
Section: Discussionmentioning
confidence: 99%